Seasonal Variations in the Structure and Function of the Gut Flora in Adult Male Rhesus Macaques Reared in Outdoor Colonies - Longbao Lv; Feiyan Zhang; Haimei Zhou; Wenxian Xiao; Yingzhou Hu; Wenchao Wang; Zhu Zhu; Fangming Zhu; Dongdong Qin; Xintian Hu (Microorganisms)
The seasonal variations that occur in the gut microbiota of healthy adult rhesus monkeys kept in outdoor groups under conventional rearing patterns and how these variations are affected by environmental variables are relatively poorly understood. In this study, we collected 120 fecal samples from 30 adult male rhesus monkeys kept in outdoor groups across four seasons and recorded the temperature and humidity of the housing facilities, as well as the proportions of fruit and vegetables in their diet. A 16S rRNA sequencing analysis showed that the alpha diversity of the gut microbiota of the rhesus monkeys was higher in winter and spring than in summer and autumn. A principal coordinate analysis (PCoA) further demonstrated notable seasonal variations in the composition and functionality of the gut microbiota in the rhesus monkeys. The phyla Firmicutes and Bacteroidetes and the genus Prevotella 9 were the significantly dominant groups in all 120 fecal samples from the rhesus monkeys. A linear discriminant analysis (LDA) effect size (LEfSe) analysis (LDA > 4) indicated that at the phylum level, Firmicutes was significantly enriched in winter, Bacteroidetes was significantly enriched in summer, and Proteobacteria and Campylobacter were significantly enriched in spring. At the genus level, Helicobacter and Ralstonia were significantly enriched in spring; Prevotella 9, Streptococcus, and Prevotella were significantly enriched in summer; and UCG_005 was significantly enriched in autumn. The beneficial genera Lactobacillus, Limosilactobacillus, and Ligilactobacillus and the beneficial species Lactobacillus johnsonii, Limosilactobacillus reuteri, Ligilactobacillus murinus, and Lactobacillus amylovorus all showed the same seasonal trend; namely, their average relative abundance was markedly greater during the winter months compared to other seasons. Compared with other seasons, carbohydrate metabolic function was significantly upregulated in winter (p < 0.01), amino acid metabolic function was relatively increased in spring, and energy metabolic function and the metabolic function of cofactors and vitamins were significantly downregulated in winter and relatively upregulated in summer. A variance partitioning analysis (VPA) and redundancy analysis (RDA) showed that the proportions of fruits and vegetables in the diet, but not climatic factors (temperature and humidity), significantly influenced the seasonal changes in the gut microbiota. These variations were related to changes in the proportions of fruits and vegetables. This research presents novel findings regarding the influence of external environmental factors on the gastrointestinal environment of rhesus monkeys.